STRUCTURE AND STATE OF DEVELOPMENT OF THE HIGH-TECHNOLOGY SECTOR OF THE NATIONAL ECONOMY OF UKRAINE - Кулік, Анна; Живолович, Андрій (SWorldJournal, 2025)
The article examines the issues of the structure and current state of development of the high-tech sector of the national economy of Ukraine and its components. Since the development of high-tech production has become a priority of state policy, Ukraine h